The Anatomy of Electricity Demand: A CGE Decomposition for Norway - Erling Holmøy (Statistics Norway, Research Department, 2005)
The paper derives a general equilibrium demand function for electricity by imposing a specific closure rule on a large CGE-model of the Norwegian economy. By a decomposition technique it quantifies the contribution from various mechanisms to the price sensitivity of aggregate electricity demand. Specifically, it identifies the contributions from substitution at the micro level, as well as changes in the industry structure to the substitution at the aggregate level. It also separates the substitution effects of equilibrium adjustments of other prices than the electricity price, and macroeconomic income effects on total demand. The direct price elasticity of aggregate electricity demand is estimated to -0.31. Within industry factor substitution contributes most to this response.
Keywords: Q41; Q43; 330; Electricity demand; Computable general equilibrium model